The ties that bind - Moravcsik, J. M. E. (Central European University Press, 2004)
"This book, like in classical times (Plato, Aristotle), treats individual and communal ethics as intertwined. At its heart lies the quartet of respect, concern for welfare of others, trust, and care as the basic communal ties. The community needs to be built on these. Acquisition and practice of other values and goods are within the frame of the four underlying "pillars". The four basic notions are attitudes and as such consist of both rational and emotional elements. Thus our ethics is based neither purely on sentiment nor purely on reason. As such they will yield us guidelines, to be filled in contextually, not rigid rule systems. Moravcsik's proposal for ethics is pluralistic but not relativistic. It does not deny some objective ground for sound communal life, but leaves many alternatives within which the four basic ties can be implemented."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved